Performance Differences Using a Vibro-Tactile P300 BCI in LIS-Patients Diagnosed With Stroke and ALS - Heilinger, Alexander; Ortner, Rupert; La Bella, Vincenzo; Lugo, Zulay R.; Chatelle, Camille; Laureys, Steven; Spataro, Rossella; Guger, Christoph (Frontiers in Neuroscience, 2018)
Patients with locked-in syndrome are typically unable to move or communicate and can be misdiagnosed as patients with disorders of consciousness. Behavioral assessment scales are limited in their ability to detect signs of consciousness in this population. Brain-computer interface (BCI) research has shown that BCI technology could supplement behavioral scales and can allow to establish communication with these severely disabled patients. In this study, we compared the vibro-tactile P300 based BCI performance in two groups of patients with locked-in syndrome (LIS) of different etiologies: stroke (n = 6) and amyotrophic lateral sclerosis (ALS) (n = 9). Two different vibro-tactile paradigms were administered to the patients to assess conscious function and command following. In the first paradigm, called VT2, a stimulator was placed on each of the patient’s wrists. The patients were asked to count the rare stimuli presented to one wrist to elicit a P300 complex to target stimuli only. In the second paradigm, called VT3, stimulators were placed on the wrists as in VT2, and one stimulator was placed on his/her back. The task was to count the rare stimuli presented to one wrist, to elicit the event-related potentials (ERPs). The VT3 paradigm could also be used for communication. For this purpose, the patient had to count the stimuli presented to the left hand to answer “yes” and to count the stimuli presented to the right hand to answer “no”. All patients except one performed above chance level in at least one run in the VT2 paradigm. In the VT3 paradigm, all 6 stroke patients and 8/9 ALS patients showed at least one run above chance. Overall, patients achieved higher accuracies in VT2 than VT3. Patients with LIS due to ALS exhibited higher accuracies that patients with LIS due to stroke, in both the VT2 and VT3 paradigms. These initial data suggest that controlling this type of BCI requires specific cognitive abilities that may be impaired in certain sub-groups of severely motor-impaired patients. Future studies on a larger cohort of patients are needed to better identify and understand the underlying cortical mechanisms of these differences.